An Application in SPSS Clementine Based on the Comparison of Association Algorithms in Data Mining - Karalök, Seren Sezen; Ersöz, Süleyman; Aktepe, Adnan (International Journal of Intelligent Systems and Applications in Engineering, 2016)
Data mining is the process of acquiring information form large data pools. In this study, associate analysis method is used.Ã‚Â  The application and comparisons are found by using 3 different algorithms from SPSS Clementine which is a data mining software. In this study, the results are varied because different associate methods are applied on. Therefore, new findings are obtained.Ã‚Â  Consequent to this, it will lead us to new strategies to develop for customers in Market Basket Analysis. This study is done by using a big supermarket data. Results are compared and reported for every each of 3 different algorithms.Ã‚Â